Fracture of piezoelectric materials with the X-FEM - Béchet, Eric; Scherzer, Matthias; Kuna, Meinhard (European Journal of Computational Mechanics, 2008)
We present an application of X-FEM to the fracture analysis of piezoelectric materials. These materials are increasingly used in actuators and sensors. Under in service loading, phenomena of crack initiation and propagation may occur due to high electromechanical field concentrations. In the past few years, the extended finite element method (X-FEM) has been applied mostly to model cracks in structural materials. The present paper focuses on the definition of new enrichment functions suitable for cracks in piezolectric structures. The approach is based on specific asymptotic crack tip solutions, derived for piezoelectric materials.